3D CNTs/Graphene‐S‐Al3Ni2 Cathodes for High‐Sulfur‐Loading and Long‐Life Lithium–Sulfur Batteries. Issue 7 (10th May 2018) - Guo, Zeqing; Nie, Huagui; Yang, Zhi; Hua, Wuxing; Ruan, Chunping; Chan, Dan; Ge, Mengzhan; Chen, Xi'an; Huang, Shaoming
Abstract: Lithium–sulfur batteries suffer from poor cycling stability at high areal sulfur loadings (ASLs) mainly because of the infamous shuttle problem and the increasing diffusion distance for ions to diffuse along the vertical direction of the cathode plane. Here, a carbon nanotube (CNT)/graphene (Gra)‐S‐Al3 Ni2 cathode with 3D network structure is designed and prepared. The 3D network configuration and the Al in the Al3 Ni2 provide an efficient channel for fast electron and ion transfer in the three dimensions, especially along the vertical direction of the cathode. The introduction of Ni in the Al3 Ni2 is able to suppress the shuttle effect via accelerating reaction kinetics of lithium polysulfide species conversion reactions. The CNT/Gra‐S‐Al3 Ni2 cathode exhibits ultrahigh cycle‐ability at 1 C over 800 cycles, with a capacity degradation rate of 0.055% per cycle. Additionally, having high ASLs of 3.3 mg cm −2, the electrode delivers a high reversible areal capacity of 2.05 mA h cm −2 (622 mA h g −1 ) over 200 cycles at a higher current density of 2.76 mA cm −2 with high capacity retention of 85.9%. The outstanding discharge performance indicates that the design offers a promising avenue to develop long‐life cycle and high‐sulfur‐loading Li–S batteries. Abstract : A carbon nanotube (CNT)/graphene (Gra)‐S‐Al3 Ni2 cathode with a 3D network structure is fabricated. Benefiting from the 3D network structure to provide efficient channels for rapid electron and ion transfer, and from the incorporation of Al3 Ni2 to promote conversion reactions of lithium polysulfide species, the CNT/Gra‐S‐Al3 Ni2 cathode shows excellent cycling stability and high capacity retention at high areal sulfur loadings.